ANALISIS KUALITAS INFORMASI AKUNTANSI KEUANGAN PADA PT.PLN (PERSERO) WILAYAH JAWA TENGAH - DIYANA KUMALA; Jaluanto SP Tyoso (FEB UNTAG Semarang, 2014)
This study aims to determine the quality of financial accounting information in PT PLN (Persero) and the factors that a constraint in optimizing the quality of financial accounting information. The method used is a qualitative method to collect existing data and compare the theory with the results of the research. Data collection techniques used in this study is the in-depth interviews to multiply pass information from the respondents and to obtain in-depth qualitative data. Analysis using data reduction techniques, Verification and Conclusions, taxonomic analysis, and presentation of data. The results showed that quality information is in accordance with the characteristics of accounting are: relevant, accurate, and timely. Personal competence in accounting data processing highly encourage the creation of quality financial statements. The presence of an existing system or application helps to improve the efficiency in the processing of data into accounting financial statements berkualitas. Keakurasian report can be seen from the proof of the correctness of the proof of the transaction or monitoring data before the data are reported each day by financial staff and every week will be checked and validated by SPV.Administrasi. Keywords: Relevant, Accurate, Timely, input control, personal competence, quality of information